Aprendo en casa en el logro de aprendizaje del niño en el área de comunicación - Llancce, Mery (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Micaela Bastidas National University of Apurímac, this study was carried out with the purpose of specifying the influence of "I learn at home" on the completion of their training in the area of ​​communication of children of five years of the Public Educational Institutions of the Initial Level of Tamburco (Peru) - 2020. The research was developed through a basic, explanatory, non-experimental and cross-sectional inquiry, with a quantitative approach, for which two research instruments were developed for each of the the variables with a total of 36 items and were applied to 106 parents and children. The processing of the data allowed to reach non-inferential and inferential findings, the test for the confirmation of the assumption was the correlation coefficient of Tau_b de Kendal, reaching the conclusion that the educational strategy "I learn at home" affects effectively and eloquently on the achievement of learning in the area of ​​communication, because its resulting statistical significance is = .028, being less than the level of significance = .05. However, the level of influence is low because t = .216.